Improved upper limits on the flavor-changing neutral current decays B -> Kl(+)l(-) and B -> K*(892)l(+)l(-) - Anderson, S; Frolov, V; Kubota, Y; Lee, S; Poling, R; Smith, A; Stepaniak, C; Urheim, J; Ahmed, S; Alam, MS; Athar, S; Jian, L; et al. (2001)
The flavor-changing neutral current (FCNC) decay was studied using Monte Carlo simulations to determine the efficiency for detecting the signal modes. The upper limits on branching fractions were obtained and no indication of a signal were obtained for the decay. Systematic and statistical errors for the process were calculated numerically.